2019
DOI: 10.1002/ett.3642
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design of an efficient handoff management strategy via velocity estimation in HetNets

Abstract: In this paper, we present an efficient handoff decision strategy and a mobility state detection (MSD) scheme for heterogeneous networks (HetNets). Due to base station (BS) densification, HetNets occasionally face unnecessary handovers and service failures. Since velocity plays a crucial role in handover process, its knowledge is imperative for effective mobility management. Furthermore, due to limited power in mobile devices, emphasis is in investigation of velocity estimators that are at service provider end.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…), can be calculated by (27) for the new feasible partition  (t) new . The minimum total coalition value V tot,min…”
Section: Hoc Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…), can be calculated by (27) for the new feasible partition  (t) new . The minimum total coalition value V tot,min…”
Section: Hoc Algorithmmentioning
confidence: 99%
“…Apart from the performance and resource allocation investigation, numerous studies have been conducted in addressing the handoff problem in SCNs. [24][25][26][27][28][29][30] A frequent handoff mitigation algorithm was developed in the work of Hasan et al 24 for an ultra-dense HetNet by classifying frequent handoff-experience users as either being fast-moving or ping-pong users. The proposed algorithm handed over fast-moving users to the macro layer, and managed ping-pong users through the modification of handoff parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have suggested several algorithms for solving and addressing HO problems. The authors in [ 49 ] described the strategy of HO decision and the estimation scheme of the mobility state to avoid service failure and unnecessary HOs (UHOs) in HetNets. The suggested model uses the HOs number, as well as the measurements of residence time, to appreciate the speed of UEs.…”
Section: Related Workmentioning
confidence: 99%
“…This method did not fully optimize the HO performance since the gap between these updating values is very big and only three fixed values are selected in accordance with UE velocity. Similarly, Tiwari and Deshmukh [10] have presented an HO decision strategy and an MSE scheme to avoid unnecessary HOs (UHOs) and service failures in HetNets. The proposed model utilizes the number of HOs and sojourn time measurements to estimate the UE velocity.…”
Section: Introductionmentioning
confidence: 99%